OPCML Methylation and the Risk of Ovarian Cancer: A Meta and Bioinformatics Analysis - Shao, Yang; Kong, Jing; Xu, Hanzi; Wu, Xiaoli; Cao, YuePeng; Li, Weijian; Han, Jing; Li, Dake; Xie, Kaipeng; Wu, Jiangping (Frontiers in Cell and Developmental Biology, 2021)
Purpose: The epigenetic inactivation of opioid binding protein cell adhesion molecule-like gene (OPCML) is critical to the pathogenesis of ovarian cancer. However, the association of OPCML methylation with ovarian cancer risk remains unclear. Therefore, we performed a meta-analysis to clarify the association. Methods: We identified eligible studies by searching the PubMed, Web of Science, ScienceDirect and Wanfang databases. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were used to determine the association of OPCML methylation with ovarian cancer risk. Meta-regression and subgroup analysis were used to assess the sources of heterogeneity. Additionally, we evaluated the relationship between OPCML methylation and ovarian cancer progression in our eligible studies. Results: Our study included 431 ovarian cancer patients and 385 controls from 8 eligible studies. The pooled OR was 33.47 (95% CI = 12.43 - 90.16) in the cancer group versus the control group under the random-effects model. The association was still significant in subgroups according to sample type, control type, methods and sample sizes (all P < 0.05). Sensitivity analysis showed that the finding was robust. No publication bias was observed in Begg’s (P = 0.458) and Egger’s tests (P = 0.261). Additionally, we found that OPCML methylation was related to III/IV (OR = 4.20, 95% CI = 1.59 - 11.14) and poorly differentiated grade (OR = 4.37; 95% CI = 1.14 - 16.78). Conclusion: Our findings suggest that OPCML methylation is associated with an increased risk of ovarian cancer and its malignant progression.